2020
DOI: 10.1200/go.20.00094
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Modern Case Series of Squamous Cell Cancer Arising in a Chronic Ulcer (Marjolin's Ulcer) of the Skin

Abstract: PURPOSE Marjolin's ulcer is an aggressive cutaneous malignancy that arises in chronic nonhealing wounds. A review of modern series describing Marjolin's ulcer would be helpful in defining optimal management strategies and expected outcomes. METHODS A systematic review was performed on October 18, 2018, by querying Medline and EMBASE. Key inclusion criteria were as follows: human studies, English language, published in 2000 or later, > 10 patients, and at least 80% of the patients having squamous cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 17 publications
2
38
0
1
Order By: Relevance
“…Among patients who demonstrated lymph node enlargement and later underwent lymph node dissection, only 25.7% had lymph node metastasis diagnosed on pathologic examination. Similar to our results, Abdi et al 57 showed that 28% of patients undergoing biopsy or dissection for clinically involved lymph nodes had pathologic involvement (24 of 85 patients). Although metastatic tumor cells may not always be found in enlarged lymph nodes, routine biopsy or lymph node dissection remains necessary.…”
Section: Lymph Node Enlargement Does Not Always Indicate Lymph Node M...supporting
confidence: 92%
“…Among patients who demonstrated lymph node enlargement and later underwent lymph node dissection, only 25.7% had lymph node metastasis diagnosed on pathologic examination. Similar to our results, Abdi et al 57 showed that 28% of patients undergoing biopsy or dissection for clinically involved lymph nodes had pathologic involvement (24 of 85 patients). Although metastatic tumor cells may not always be found in enlarged lymph nodes, routine biopsy or lymph node dissection remains necessary.…”
Section: Lymph Node Enlargement Does Not Always Indicate Lymph Node M...supporting
confidence: 92%
“…So sánh với kết quả nghiên cứu của một số tác giả khác: Trong nghiên cứu của tác giả Lê Thế Trung 100% các bệnh nhân là ung thư biểu mô tế bào gai (ung thư biểu mô tế bào vảy -SCC) [4]; Trong báo cáo tổng hợp của Abdi M.A. trên 599 bệnh nhân thấy rằng ung thư biểu mô tế bào vảy chiếm tới 92% [5].…”
Section: đặC đIểm Dịch Tễ Lâm Sàngunclassified
“…In particular, pressure skin ulcers, skin ulcers complicated by diabetes, and venous ulcers of the lower extremities are the most common CSUs [ 1 ]. As a common and frequently occurring disease, CSUs seriously threaten human health and severe cases may require amputation, cause cancer, and have fatal outcomes [ 2 , 3 ]. With the migration of the disease and the occurrence of related complications, patients and their families have to bear the huge economic burden and psychological obstacles associated with CSUs.…”
Section: Introductionmentioning
confidence: 99%